Ethical infrastructure the road to moral management - Bergoč, Jana Nadoh (Cambridge Scholars Publishing, 2019)
This book deals with the field of organization management and is based on the scientific discoveries of business ethics, which introduce concepts in organization research that traditionally did not merit a place in managerial theories. These include the issue of organization ethics, ethics management, and the development and implementation of ethical infrastructures within organizations. The book analyses the impact that all of the above have on the moral behaviour of managers and other members of organizations. It shows the presence and development of ethical infrastructures in organizations, the relationship between individual elements of the existing ethical infrastructures, and their effect on the moral behaviour of managers in companies.The subject of ethical infrastructures is a unique and under-researched area. This book will serve to diminish this gap by providing a clear overview of a variety of subjects that influence the way ethics is institutionalized in organizations and by stimulating not just knowledge, but also an understanding of the concept of ethical infrastructure and the place it has within each individual organization.